Changes induced in the permeability barrier of the yeast plasma membrane by cupric ion. - Ohsumi, Y (1988)
A specific effect of Cu2+ eliciting selective changes in the permeability of intact Saccharomyces cerevisiae cells is described. When 100 microM CuCl2 was added to a cell suspension in a buffer of low ionic strength, the permeability barrier of the plasma membranes of the cells was lost within 2 min at 25 degrees C. The release of amino acids was partial, and the composition of the amino acids released was different from that of those retained in the cells. Mostly glutamate was released, but arginine was mainly retained in the cells. Cellular K+ was released rapidly after CuCl2 addition, but 30% of the total K+ was retained in the cells. These and other observations suggested that Cu2+ caused selective lesions of the permeability barrier of the plasma membrane but did not affect the permeability of the vacuolar membrane. These selective changes were not induced by the other divalent cations tested. A novel and simple method for differential extraction of vacuolar and cytosolic amino acid pools by Cu2+ treatment was established. When Ca2+ was added to Cu2+-treated cells, a large amount of Ca2+ was sequestered into vacuoles, with formation of an inclusion of a Ca2+-polyphosphate complex in the vacuoles. Cu2+-treated cells also showed enhanced uptake of basic amino acids and S-adenosylmethionine. The transport of these substrates showed saturable kinetics with low affinities, reflecting the vacuolar transport process in situ. With Cu2+ treatment, selective leakage of K+ from the cytosolic compartment appears to create a large concentration gradient of K+ across the vacuolar membrane and generates an inside-negative membrane potential, which may provide a driving force of uptake of positively charged substances into vacuoles. Cu2+ treatment provides a useful in situ method for investigating the mechanisms of differential solute pool formation and specific transport phenomena across the vacuolar membrane.